Analisis Akuntabilitas Politik Reses, Studi Tentang Kegiatan Reses Anggota DPRD Provinsi Jawa Tengah - Rachmad Hendriyanto; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2014)
Recess as one vertically upward aspirations of the people to the government , through the Central Java Provincial Parliament visits to selected areas (constituencies) . Mechanisms are rarely recess in the publication , as well as the rationality of the implementation and budgeting are less accommodate the aspirations of society , it will be a problem of political accountability as well as the development and welfare of the people of Central Java . Communication patterns that do board members when the recess is also not clear , so it was less than the maximum aspiration .Based on these problems the research is intended to determine the mechanism of the Central Java Provincial Parliament recess actual , political accountability and review . The method used in this study is a qualitative research method . With the primary data source through in-depth interviews with relevant parties , such as the Central Java Provincial Parliament and their constituents . Then the kinds of observations , and collect the documents necessary to be able to assess the problem.The results of this study , namely , the method recess DPRD members in part of Central Java province varied enough to be able to capture the aspirations constituents , be it to do with the budget , social issues , Government policy , as well as other problems . Then the initiative of the board members to continue and fight for these aspirations to be accommodated is still minimal , only a few members who can realize it . Overall conclusion is that political accountability activities Recess Central Java Provincial Parliament still less when viewed from several aspects of public accountability of Parliament to the public administration.Keywords : Political Accountability , Recess , Rationality